2001
DOI: 10.2355/isijinternational.41.670
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Research on High-speed Conventional Slab Continuous Casting of Carbon Steels.

Abstract: Two decades ago the casting speed of the conventional slab continuous caster was increased stepwise to a level over 2 m/min. Henceforth, the casting speed has been remained a similar level. In this review the reasons for constraining the casting speed are discussed. As a result the constraints of the high-speed casting are thought mold powder entrapment and longitudinal facial crack occurring in high-speed casting.Some measures to prevent the mold powder entrapment and the longitudinal facial crack are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 19 publications
(28 reference statements)
2
35
0
3
Order By: Relevance
“…Um modelo físico em acrílico, construído em escala = 0, 6 critério de similaridade. O mapa de velocidades foi determinado por meio da técnica PIV.…”
Section: Materiais E Métodosunclassified
“…Um modelo físico em acrílico, construído em escala = 0, 6 critério de similaridade. O mapa de velocidades foi determinado por meio da técnica PIV.…”
Section: Materiais E Métodosunclassified
“…Stokes collision [38,55,58,63,64] may also contribute to the growth of inclusions. Zhang and Pluschkell recently have combined classic homogenous nucleation theory, thermodynamic analysis, and a multiple size grouping methodology to develop a fundamental model of nucleation and growth of alumina inclusions in steel using numerical simulation.…”
Section: A Indigenous Inclusions In Steelmentioning
confidence: 99%
“…[4] adding deoxidizer, particles nucleate or precipitate, and quickly grow. Starting from the rapid supersaturation that occurs when alloys are released and dispersed into the melt, homogeneous nucleation is very fast, occurring in 1 to 10 ms. [54] Inclusion growth is controlled by diffusion of the deoxidization elements and oxygen, [38,40,[55][56][57][58] local thermodynamics, [31,38,42,[59][60][61][62] Ostwald ripening, [40,55,58,63,64] and Brownian collisions [38,40,55,56,58] when inclusions are smaller than 1 mm.…”
Section: A Indigenous Inclusions In Steelmentioning
confidence: 99%
“…In the actual caster such conditions would eventually lead to the entrainment of flux. 24) The larger presence of green areas in SEN-3 indicates a more stable meniscus. It is also important to emphasize the different frequencies of meniscus oscillations comparing the SENs.…”
Section: Cfd Analysis Of Meniscus Stabilitymentioning
confidence: 99%
“…Some slab casting submerged nozzle designs induce strong meniscus instability and high amplitude oscillations of liquid steel in the mold. 6) Takatani et al 7) found that in a conventional slab mold the horizontal velocity under the meniscus fluctuates strongly. Using a physical model Yoshida et al 8) identified downward flows at the meniscus along the outer surface of the SEN due to the existence of differential pressure in this region.…”
Section: Introductionmentioning
confidence: 99%